Cardiovascular risk assessment in population from urban and sub urban areas of Eastern part of Odisha, India - Patro, Shubhransu; Behera, Surendra N.; Behera, Basanta K.; Misra, Gagan C. (International Journal of Advances in Medicine, 2016)
Background: Cardiovascular disease (CVD) is a leading cause of death in the world. The aim of the study was to assess cardiovascular risk factors in population from urban and sub urban areas of eastern part of Odisha, India. Methods: We conducted an observational study; total 67 individuals (21 women, 46 men) were recruited from the population, aged 30 to 59 years, to evaluate their cardiovascular risk factors by pre-designed structured questionnaire and clinical and laboratory data were collected over a period of 6 months. Results: The prevalence of major CVD risk factors was: hypertension 28.3%, diabetes 38.8%, elevated total cholesterol/HDL ratio 38.8 %, obesity 62.6 % and current smoking 28.3%.The score of ≥4 was obtained more among the 40–49 year old age group than the 30-39 and 50-59 year old age groups (≥2) and the risk factor score of ≥3 was significantly more in the higher income group as compared with the lower income group (74% vs. 26%). A high-risk dietary pattern was found to be significantly more in the literate group as compared with the illiterate group (32.2% vs. 25%). Conclusions: This study concludes that the high prevalence of CVD and its risk factors is due to lack of awareness and special attention should be given to changing life style and dietary control among a comparatively young male population from urban and sub urban areas of eastern part of Odisha.